Kelayakan Bahan Ajar Biomodif Materi Animalia untuk Siswa Kelas X SMA - Isniawati, Mei Dwi; Malahayati, Eva Nurul; Anggraini, Dian Puspita (FKIP Universitas Wisnuwardhana, 2022)
This research aim to knowing feasibility of BIOMODIF (Biologi Modul Interaktif) for class X. Research model applied is R&D (Research and Development) with survey method. The instruments utilized in this research were questionnaire. The sample of this research were 3 linguist, 3 material expert, 3 media expert and IT expert. The data analysis technique is by calculating the feasibility score with percentage range were adaptation from Sugiyono. The results of this research obtained a feasibility value of 91%, 90%, 78,8% and 92,5%, which are included within the suitable category of teaching materials. Conclusion from this study indicate that BIOMODIF is acceptable to be used for biology teaching materials of Animalia theory at class X.